Выполните действия:
а)
-----------------------------------------------------------------------------------------
в)
Упростите выражение:
а) (3ab+5a-b)-(12ab-3a)=3ab+5a-b-12ab+3a=8a-9ab-b
Выполните действия:
а)![(3ab+5a-b)-(12ab-3a)=3ab+5a-b-12ab+3a=(5a+3a)+(3ab-12ab)-b=8a-9ab-b](/tpl/images/0039/4501/1ed07.png)
-----------------------------------------------------------------------------------------
в)![(2a-3c)(a+2c)=2a^{2}+4ac-3ac-6c^{2}=2a^{2}+(4ac-3ac)-6c^{2}=2a^{2}+ac-6c^{2}](/tpl/images/0039/4501/a62af.png)
Упростите выражение:
а) (3ab+5a-b)-(12ab-3a)=3ab+5a-b-12ab+3a=8a-9ab-b
в)![(2a-3c)(a+2c)=2a^{2}+4ac-3ac-6c^{2}=2a^{2}+ac-6c^{2}](/tpl/images/0039/4501/e2d00.png)